The accidental playground Brooklyn waterfront narratives of the undesigned and unplanned - Campo, Daniel; ebrary, Inc. (New York : Empire State Editions, 2013)
"The Accidental Playground explores the remarkable landscape created by individuals and small groups who occupied and rebuilt an abandoned Brooklyn waterfront in Williamsburg. Without formal authority, capital, professional assistance, grand vision, consensus, or coordination with each other, these "vernacular" builders transformed a vacated waterfront railroad yard into a unique setting for recreation and creative endeavor. With the Manhattan skyline as its backdrop, the collapsing piers, eroded bulkhead, and remaining building foundations of the former Brooklyn Eastern District Terminal (BEDT) became the raw materials for various forms of waterside leisure and social spaces. Lacking predetermined rules governing its use, this waterfront evolved into the home turf for unusual and sometimes spectacular recreational, social, and creative subcultures. These included skateboarders who built a short-lived, but nationally renowned skatepark; a twenty-five-piece "public" marching band, fire performance troupes, and a variety of artists, photographers, and filmmakers. At the same time the site also served basic recreational needs of local residents. Collapsing piers became great places to catch fish, sunbathe, or take in the Manhattan skyline; the foundation of a demolished warehouse became an ideal place to practice music or skateboard; rubble-strewn earth became a compelling setting for film and fashion shoots; broken bulkhead became a beach; and thick patches of weeds dotted by ailanthus trees became a jungle. Drawing on a rich mix of documentary strategies including observation, ethnography, photography, and first-person narrative, Daniel Campo probes this accidental playground, allowing those who created it to share and examine their own narratives, perspectives, and conflicts. The multiple constituencies of this Williamsburg waterfront were surprisingly diverse, their stories colorful and provocative. When taken together, Campo argues, they suggest a radical reimagining of urban public space, the waterfront, and the practices by which they are created and maintained. The Accidental Playground, which treats readers to an utterly compelling story, is an exciting and distinctive contribution to the growing literature on the unplanned and the undesigned spaces and activities in cities today"--
Machine generated contents note: -- Chapter 1 - Discovering and Engaging a Waterfront -- Chapter 2- The Rise and Fall of Shantytown Skatepark -- Chapter 3- March and Burn: Practice, Performance and Leisure without a Plan -- Chapter 4- Outside Art: Exploring Wildness and Reclamation at the Water's Edge -- Chapter 5- Local Tales: Hanging Out and Observing Life on the Waterfront -- Chapter 6- Residential Life: Hardship and Resiliency on the Waterfront -- Chapter 7- Neighbors Against Garbage: Activism and Uneasy Alliances on the Waterfront -- Chapter 8- Unplanned Postscript: Dogs, Sunsets, Rock Bands and the Governance of a Waterfront Park -- Chapter 9- Planning for the Unplanned.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Brooklyn Eastern District Terminal; Recreation -- New York (State) -- Brooklyn (New York); Communities -- New York (State) -- Brooklyn (New York); Waste lands -- Recreational use -- New York (State) -- Brooklyn (New York); Waterfronts -- Recreational use -- New York (State) -- Brooklyn (New York); Electronic books